Eksistensi Pendidikan Pesantren dalam Arus Perubahan - Ahmad Royani (IAIN Ponorogo, 2018)
Rapid change, demanding the ability of pesantren to respond quickly, precisely, and adaptively.In this paper talks about the existence of pesantren education in the face of the flow of change. This research is focused on the existence conducted by As-Shafi'i boarding school (pesantren) in the flow of change. The approach used in this study is a case study experienced by remote educational institutions that boarding boarding schools As-syafi'I in existence maintain the institution of boarding school. The theory used in this study uses Talcott have four things called AGIL: Adaptation Goal attainment, Integration, Latency. Concluded that the existence of pesantren education in the flow of change as follows; Thefirst adaptation conducted by the boarding school As-Syafi'I is to know in detail the existing needs in the community. Second, the development of personality aims to prepare the students and the public to have the knowledge of religion and general science in order to become human beings who are able to practice their knowledge. Third, integrating and integrating school and pesantren systems Thefour patterns of As-Syafi'I boarding school institutions are building networking with all components of society, santri guardian, government in building pesantren. قد طلب التغير السريع بقدرة المدرسةالداخلية على الاستجابة بسرعة ودقة وتكيف. تتحدث هذه الكتابةعن وجود تعليم المدرسةالداخليةفي مواجهة تدفق التغيير. و يركز هذا البحث على وجود مدرسة الشافعي الداخلية في تدفق التغيير. وأما المنهج المستخدم في هذه الدراسة هو دراسة حالة في مؤسسة التعليمية النائية ، وهي مدرسة الشافعي الداخلية في احتفاظ وجودهاكالمؤسسة التربوية الإسلامية الداخلية. و تستخدم هذه الدراسةالنظرية التي تقدمت بها تلكوت فيرسونو قيل لكييستطيع نظام التنظيم الاجتماعي أنيحتفظ وجودهفيجب أن يكون النظام له أربعة أشياء تسمى(AGIL) و هيالتكيف (adaptation) و تحقيق الأهداف (goalattainment)و التكامل (integration) و التأخر (latency).و من نتائج الدراسة يستطيع الباحث أن يستنتجبأن وجود التربيةفيالمدرسةالداخليةفي تدفق التغيير هو على النحو التالي : أولا، التكييف الذي أجرته المدرسة الشافعي الداخلية هو معرفة احتياجات المجتمع الحالية بالطريقة المباشرة. و ثانياً، يهدف تدريب الشخصية إلى إعداد الطلاب والمجتمعلأن يتقنو المعرفة الدينية والمعرفة العامة لكي يصبحو الناس الذينلهمقدرة على ممارسة معرفته. و ثالثًا، وإدماج العامة ونظامالمدرسةالداخلية لإنتاج أجيال موثوقةفي حقولهم. و رابعًا، الأنماط التي تنفذها المدرسة الشافعي الداخلية هي بناء التواصل مع جميع المكونات و هم المجتمع وأولياء الطلاب والحكومة لبناء المدارس و تقدمه. بالإضافة إلى ذلك، فإن الاستثمار الاجتماعي للبرنامج الداخلي هو من نشاطالمدرسة الشافعي الداخلية الذي يهدف إلى خلق الجيل المستقل المفيد في الحياة المجتمعية في وقت مستقبل.